Consistent long‐term Holocene warming trend at different elevations in the Altai Mountains in arid central Asia - Zhiguo Rao; Haichun Guo; Jiantao Cao; Fuxi Shi; Guodong Jia; Yunxia Li; Fahu Chen (Journal of Quaternary Science, 2020)
Recent results indicate contrasting Holocene moisture histories at different elevations in arid central Asia (ACA). However, relatively little is known about Holocene temperature changes at different elevations. Here we report an independently dated peat brGDGTs‐based MBT' 5ME record from the Narenxia peatland (NRX) in the southern Altai Mountains. The record suggests a long‐term warming trend since ~7.7 cal. kyr bp , with a warmer stage during ~7–5.5 cal. kyr bp , a cold stage during ~5.5–4 cal. kyr bp , and a warming trend over the last ~4 kyr. The long‐term warming trend indicated by the NRX MBT' 5ME record is largely consistent with Holocene temperature records from nearby sites covering an altitudinal range of ~1700–4100 m above sea level. This consistent long‐term warming trend at different elevations differs from the long‐term Holocene drying/wetting trends at high/low elevations of the Altai Mountains. We propose that the warming trend and consequent permafrost thawing at high elevations could have resulted in increased meltwater runoff, which would have contributed to the long‐term wetting trend at low elevations. Our findings potentially provide an improved understanding of regional climate change and associated water resource availability, with implications for their possible future status.